Use of social networks in emerging adults: The role of irrational beliefs - Stojković, Irena; Vukosavljević-Gvozden, Tatjana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. The use of online social networks has become widespread among the young. Although it may have beneficial effects, it has been established that some people develop problematic or excessive use of social networks which may negatively impact their psychosocial functioning. Objective. The aim of the present study was to investigate social networks use among emerging adults and to explore whether irrational and rational beliefs as conceptualized within the Rational-Emotive & Cognitive-Behavior Therapy (RE&CBT) framework predict problematic social networks use. Following RE&CBT framework, we hypothesized that irrational beliefs are positively, and rational beliefs negatively related to problematic social networks use. Methods. The sample included 210 emerging adults (age range 18–26, M = 21.08, SD = 2.02), 59.0% females. Serbian version of the General Attitude and Belief Scale (SGABS) was used for the assessment of irrational and rational beliefs. Serbian version of Internet Addiction Test was adapted for the assessment of problematic social networks use. Results. The results supported the hypothesis that irrational beliefs are positively related to problematic social networks use. When controlling for intercorrelations between beliefs, demands for love and approval from others stood out as a single significant predictor of problematic social networks use. Rational beliefs were unrelated to problematic social networks use, thus not supporting the hypothesis. Conclusion. The results suggest that RE&CBT approach, which has been proven to be efficacious in prevention of various problems of psychosocial functioning may also provide framework for supporting young people to use social networks in a constructive way.